1)=8а²(в²-9с²)=8а²(в-3с)(в+3с).
2)=2(х²-12ху+36у²)=2(х-6у)².
3)=-2а(4а4-4а²+1)= -2а(2а²-1)².
4)=5(а³-8в6)=5(а³-(2в²)³)=5(а-2в²)(а²+2ав²+4в4)
5)=(а³+а²)-(ав-а²в)=а²(а+1)-ав(1+а)=(а+1)(а²-ав)=а(а+1)(а-в)
6)=с4(а-1)-с²(а-1)=(а-1)(с4-с²)=с²(а-1)(с²-1)=с²(а-1)(с-1)(с+1).
1)=(х-у)²-7²=(х-у-7)(х-у+7)
2)=а²-(3в-с)²=(а+3в-с)(а-3в+с)
3)=(в³)²-(2в²-3)²=(в³+2в²-3)(в³-2в²+3).
4)=(m³+3³n³)+(m+3n)²=(m+3n)(m²-3mn+9n²)+(m+3n)²=(m+3n)(m²-3mn+9n²+m+3n).
5)=x²-y²+2x+4y-3=(x²+2x+1)-(y²-4y+4)=(x+1)²-(y-2)²=(x+y-1)(x-y+3).
Відповідь:
1) f(1)=-3×1² + 2×1=5
2)f(0)=0
3) f(
)=-3×(
)²+2×
=-
+
=![\frac{1}{3}](/tpl/images/0801/2541/5506e.png)
4) f(-2)= 3×(-2)²+2×(-2)=12-4=6
1) 0=-3x²+2x
x(2-3x)=0; x=0;
2-3x=0; -3x=-2; x=![\frac{2}{3}](/tpl/images/0801/2541/d1391.png)
2) -3x²+2x=-1
-3x²+2x+1=0
D=ᵇ²-4ac= 2²-4×(-3)×1=4+12=16=4²
x₁₂=![\frac{-b±\sqrt{D} }{2a}](/tpl/images/0801/2541/ebbf0.png)
x₁=![\frac{-2+4}{-6} =-\frac{1}{3}\\](/tpl/images/0801/2541/f6851.png)
x₂=![\frac{-2-4}{-6} =1](/tpl/images/0801/2541/f4d85.png)
3)-3x²+2x+56=0
D=676=26²
x₁=-4
x₂=![\frac{28}{6}](/tpl/images/0801/2541/e4c24.png)
Пояснення:
Значення функції дорівнює f(x)